Nanocoral CuCoNiS4: Enhancement in the electrochemical capacitance by Ni incorporation in CuCo2S4. (15th August 2022) - Sethulakshmi, N.; Mohan, Ajay; Sharma, Sudhanshu
Abstract: Nanocoral structures of CuCo2 S4 and CuCoNiS4 were synthesized using hydrothermal method. Excellent electrocatalytic response with oxygen evolution reaction (OER) at an onset potential of 1.27 V (vs. RHE) is observed in CuCo2 S4 . On replacement of half of Co ions by Ni, the electrocatalytic activity reduced with the disappearance of OER. Electrochemical impedance studies indicated that on Ni substitution, the impedance behaviour changes from resistive to a nearly capacitive or pseudocapacitive behaviour. EIS equivalent circuit fitting model showed bulk resistance (Ω·cm 2 ) values of 2.16 and 1.65 for CuCo2 S4 and CuCoNiS4 respectively. However, specific capacitance increased to 308 F/g in Ni substituted thiospinel, CuCoNiS4 compared to 83 F/g in CuCo2 S4 at a current density of 3 A/g and at a potential of 0.85 V (vs. Ag/AgCl). For a higher current loading of 10 A/g, CuCoNiS4 showed a specific capacitance of 177 F/g. In this work, we report the key role played by octahedral Ni ions in Cu – Co based thiospinels. Graphical abstract: Unlabelled Image Highlights: Morphological difference of two composites CCS and CCNS, synthesized by hydrothermal method, was evident from SEM images. Capacitive characteristics of CCNS increased, while oxygen evolution trend decreased, compared to CCS. Impedance studies on the materials showed transition from Warburg diffusion in CCS to semi-infinite diffusion in CCNS. For a potential of 0.85V, CCNS showed a specific capacitance of 308F/g at 3A/g current density, compared to 83F/g for CCS.